Morphing of the Frontal View: Rhinoplasty as a Surface Contour Operation - Golan, Izak; Khodaei, Iman; Vasilenko, Irina; Palma, Pietro (Facial Plastic Surgery, 2025)
Frontal view morphing is needed for better preoperative consultation and simulation process in rhinoplasty. Restoration of the correct light–shadow interactions in rhinoplasty demands a firm appreciation of the underlying nasal structures. Chiaroscuro is a painting technique of dark and light contrasts that can be utilized in the morphing process, enabling the surgeon to explain possible results. Patients undergoing surgery in 2019. Encounters were divided into three. First visit: history taking, a list of desires and physical examination, photography. Second visit: photo analysis was presented as well as the hypothesis of correction expressed by morphing (morphing with Adobe Photoshop software). We termed the differences between light and shade of the lateral nasal walls, the dorsum and the brow dome line and nose cheek line as the “Chiaroscuro of the nose.” This term is significant in the process of morphing of the frontal view. We used this method of morphing in the simulation process of 126 patients. The age range was 15 to 59 years old. A total of 67% (84) were females and 33% (42) were males. A total of 43% (54) of the cases were revision cases. At the postoperative visits, all patients were more satisfied with their operative result than with their “morphed” simulation. The chiaroscuro concept of the nose is an essential step in the analysis and morphing processes of the frontal view, and a logical tool in creating a realistic surgical game plan. The morphing of the frontal view enables the surgeon and patients to discuss the possible result with more details and refinements. Morphing may be a good option to educate young surgeons in both preoperative consultation and at the operating theater.
Keywords: preoperative simulation; rhinoplasty; chiaroscuro painting; rhinoplasty morphing frontal view; simulation and morphing in rhinoplasty